The Dalit Women Movement in Nepal: A Study from the Intersectional Perspective - Bishowkarma , Megha Bahadur (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
The issue of the Dalit women's movement in Nepal has been an important debate in the sociopolitical and academic arena from the initial phase of the sixtieth decade. Caste-based discrimination, economic exploitation, and social exclusion against Dalit women and Dalits, as well as harsh untouchability-related laws enforced by the Varna-based caste system and Hindu rulers, were the main causes of the Dalit women's movement in Nepal. Dalit women have been compelled to live in the face of many caste-based injustices and atrocities for centuries, in which they are consistently deprived access to the state's many opportunities. In Nepal, the Dalit women's movement has been instrumental in changing many facets of traditional society, promoting gender equality, ending caste-based discrimination and untouchability, and obtaining rights for Dalit women alongside other marginalized women. This study investigates how the Dalit women’s movement is perceived and how the caste system affects the lives and careers of Dalit women in Nepal by means of the author’s auto-ethnography and in-depth interviews taken with Dalit women. The study not only discloses how the caste system controls the power regime and state mechanisms, it also exposes how it influences the sociocultural and political structures. Indeed, the initial phases of the Dalit women's movement and the Badi women's movement were effective in creating pressure to bring about sociopolitical empowerment, reducing caste-based discrimination, and strengthening leadership in public domains, despite certain controversies of the Dalit women-led non-governmental organizations that were activated in the name of the Dalit women's struggle after the democratic era began in 2046. In order to free themselves from centuries of severe repression and many forms of discrimination as so-called lower-caste, lowest-class, and highly marginalized women, this paper suggests the unification among Dalit women and the conduction of their strong and result-oriented struggle in Nepal.